2017
DOI: 10.1016/j.ejcb.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Elastic ‘tethers’ connect separating anaphase chromosomes in a broad range of animal cells

Abstract: We describe the general occurrence in animal cells of elastic components ("tethers") that connect individual chromosomes moving to opposite poles during anaphase. Tethers, originally described in crane-fly spermatocytes, exert force on chromosome arms opposite to the direction the anaphase chromosomes move. We show that they exist in a broad range of animal cells. Thus tethers are previously unrecognised components of general mitotic mechanisms that exert force on chromosomes and they need to be accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(67 citation statements)
references
References 25 publications
4
63
0
Order By: Relevance
“…This was part of our experimental protocol (described below). Arm fragments produced in anaphase taxol-treated cells behave as they do in not-treated cells: they move backwards across the equator toward their partner chromosomes moving to the opposite pole (Figures 2 , 3 ), as described previously in crane-fly spermatocytes (LaFountain et al, 2002 ; Sheykhani et al, 2017 ) and other animals cells (Forer et al, 2017 ). In our experiments arm-fragment velocities in taxol-treated cells were considerably faster than the velocities of the associated chromosomes (Figure 4 ), as previously reported in control cells (LaFountain et al, 2002 ; Sheykhani et al, 2017 ).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…This was part of our experimental protocol (described below). Arm fragments produced in anaphase taxol-treated cells behave as they do in not-treated cells: they move backwards across the equator toward their partner chromosomes moving to the opposite pole (Figures 2 , 3 ), as described previously in crane-fly spermatocytes (LaFountain et al, 2002 ; Sheykhani et al, 2017 ) and other animals cells (Forer et al, 2017 ). In our experiments arm-fragment velocities in taxol-treated cells were considerably faster than the velocities of the associated chromosomes (Figure 4 ), as previously reported in control cells (LaFountain et al, 2002 ; Sheykhani et al, 2017 ).…”
Section: Resultssupporting
confidence: 74%
“…Aspects of our experiments peripheral to how force is produced with severed kinetochore microtubules deal with further evidence that elastic “tethers” cause the movements of arm fragments (cut from telomere-containing ends of anaphase chromosomes) toward their separating partner chromosomes (across the equator). The experimental evidence that these movements are due to elastic tethers that extend between chromosomes and not to interzonal microtubules (discussed in LaFountain et al, 2002 ; Forer et al, 2017 ; Paliulis and Forer, 2018 ) basically is that arm-fragment movement stops after ablation of either the moving telomere or the partner′s telomere (to which the fragment is moving). Our results on movements of arm fragments in taxol-treated cells add to this argument because taxol-treatment eliminates the transport properties of crane-fly spermatocyte spindle microtubules: akinetic pieces of chromosomes in not- treated crane-fly spermatocytes move poleward, but akinetic pieces in taxol-treated spermatocytes do not move poleward, showing that the non-dynamic spindle microtubules in taxol-treated cells no longer support their movement (LaFountain et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomes that did not shorten may not have been affected as the laser failed to sever a tether, or these chromosome arms were not tethered. The relaxation of only half of PtK2 chromosomes is consistent with findings that only half of chromatids are tethered in crane-fly spermatocytes [24][25][26]. When severing chromosomes during transport, kinetochore attached arms successfully segregated while chromosome fragments either did not move significantly, briefly travelled towards the opposing pole and stopped, or fully travelled to and remained at the sister side.…”
Section: Discussionsupporting
confidence: 70%
“…found that two of four sister chromatids in crane-fly spermatocytes were linked by a physical tether connecting their telomere regions such that a 'cross-polar' force elongated segregating chromosomes and moved severed chromosome fragments through the cell [24]. Recent studies confirmed these findings in crane-fly spermatocytes and found that chromosome elongation could be reduced by severing this tether [25,26]. Laser microsurgery can help deduce the mechanistic basis for chromosomal elongation in PtK cells by attempting to sever the tether and examining length change, or by generating chromosome fragments -which are presumably attached to the tether-and examining their travel.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation